Association between neurodevelopmental disorders in congenital heart disease and changes in circulatory metabolites and gut microbiota composition - An, Jia; Wang, Qiang; Bai, Zihao; Ma, Siyu; Yang, Zhaocong; Yu, Di; Mo, Xuming (Frontiers in Microbiology, 2025)
BackgroundNeurodevelopmental disorder (ND) has emerged as a critical factor affecting the long-term quality of life among patients with congenital heart disease (CHD). The aim of this study was to provide a multi-omics perspective on the mechanisms of ND.MethodsWe analyzed the serum metabolome and gut microbiome of children with ND and non-ND (NND) in CHD populations.ResultsIn this prospective observational study, we identified associations between serum metabolites, gut microbial, and ND. Linolenic acid was most closely related to neurodevelopmental outcomes, showing positive correlations with multiple neurodevelopmental domains. Among the gut microbiota, the Escherichia genus was most strongly associated with neurodevelopmental outcomes, and negative correlations with neurodevelopmental domains.ConclusionThis multi-omics study reveals significant association between altered serum metabolites, gut microbiota dysbiosis, and neurodevelopmental outcomes in children with CHD. The microbes and metabolites identified here may contribute to addressing the challenge of ND in the CHD population. Based on our findings, therapeutic strategies to reduce the risk of ND could be developed, including targeted manipulation of the gut microbiota and metabolites.